Cross-Species Sequence Comparisons: A Review of Methods and Available Resources - Frazer, Kelly A.; Elnitski, Laura; Church, Deanna M.; Dubchak, Inna; Hardison, Ross C. (Genome Research, 2003)
With the availability of whole-genome sequences for an increasing number of species, we are now faced with the challenge of decoding the information contained within these DNA sequences. Comparative analysis of DNA sequences from multiple species at varying evolutionary distances is a powerful approach for identifying coding and functional noncoding sequences, as well as sequences that are unique for a given organism. In this review, we outline the strategy for choosing DNA sequences from different species for comparative analyses and describe the methods used and the resources publicly available for these studies.
10.1101/gr.222003